2017
DOI: 10.1155/2017/9584278
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diabetic Cardiomyopathy by Cardiovascular Magnetic Resonance T1 Mapping: Correlation with Left-Ventricular Diastolic Dysfunction and Diabetic Duration

Abstract: Purpose To quantify extracellular matrix expansion with the cardiovascular magnetic resonance (CMR) T1 mapping technique and the derived extracellular volume fraction (ECV) in diabetic cardiomyopathy (DbCM) patients and to detect the relationship among ECV, duration of diabetes, and diastolic function. Materials Thirty-eight patients with diabetic cardiomyopathy (20 males, age 54.6 ± 8.6 years) and thirty-two matched normal controls (15 males, age 51.4 ± 13.6 years) were prospectively enrolled. All of them wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…An inflammatory cardiomyopathy has previously been linked with several viruses including influenza 28 but its association with COVID-19 remains unclear. Moreover, similar patterns of non-ischaemic late gadolinium enhancement are commonly observed in patients with hypertension and diabetes mellitus 27 in the absence of myocarditis. Regardless of the mechanism, the prognostic value of late gadolinium enhancement across multiple disease states probably warrants long-term follow-up.…”
Section: Discussionsupporting
confidence: 63%
“…An inflammatory cardiomyopathy has previously been linked with several viruses including influenza 28 but its association with COVID-19 remains unclear. Moreover, similar patterns of non-ischaemic late gadolinium enhancement are commonly observed in patients with hypertension and diabetes mellitus 27 in the absence of myocarditis. Regardless of the mechanism, the prognostic value of late gadolinium enhancement across multiple disease states probably warrants long-term follow-up.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, the final study cohort comprised 71 T2DM patients and 30 healthy controls (proportion of males 56.7% vs. 57.7%, p = 0.92; mean age 53.99 ± 11.15 vs. 53.23 ± 8.59 years, p = 0.74). Based on the duration of diabetes [ 7 , 20 ], all T2DM patients were categorized as either newly diagnosed DM (duration of diabetes ≤ 5 years, n = 31) or longer-term DM (duration of diabetes > 5 years, n = 41). The baseline characteristics of the T2DM patients and healthy volunteers are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…While some conditions such as myocardial infarction, cardiac amyloid, and HCM with LGE show a significant increase in the ECV [ 19 , 20 ], more subtle differences are seen in conditions with less myocardial damage, such as T2DM or HCM without LGE. Wong’s study [ 6 ] and our previous study [ 21 ] demonstrated that T2DM patients had a slightly but significant increased ECV. In the present study, there were minor but significant differences in the ECVm between the T2DM patients and the healthy subjects; however, the ECVsyn did not differ.…”
Section: Discussionmentioning
confidence: 89%